Normative values and functional fitness in 60-to-69 year-old men - Leandro Ferreira; Sebastião Gobbi; Tânia R. Bertoldo Benedetti; Giovana Zarpellon Mazo; Marize Amorim Lopes (Universidade Federal de Santa Catarina, 2010)
The objective of this study was to develop normative reference of functional fitnessand an overall functional fitness index (OFFI) for 60- to 69-year-old men. A total of 112 oldermen living in Florianópolis/SC and Rio Claro/SP, who had been participating in structured andsupervised physical activities on a regular basis for the past 6 months, were evaluated by theAAHPERD test battery. This battery consists of five tests that evaluate flexibility, coordination,balance and agility, muscle strength, and aerobic capacity. Percentile scores were calculated forthe raw scores obtained in each test and the sum of percentiles was used as the OFFI. The 20th,40th, 60th and 80th percentiles were taken as limits to classify the components and OFFI asvery weak, weak, fair, good, and very good, respectively. The development of normative referencemight be useful for professionals to improve the evaluation, supervision and prescriptionof physical activity to older men.